2011
DOI: 10.5194/acp-11-2503-2011
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale convective systems observed during AMMA and their impact on the NO<sub>x</sub> and O<sub>3</sub> budget over West Africa

Abstract: Abstract. During the "African Monsoon MultidisciplinaryAnalysis" (AMMA) field phase in August 2006, a variety of measurements focusing on deep convection were performed over West Africa. The German research aircraft Falcon based in Ouagadougou (Burkina Faso) investigated the chemical composition in the outflow of large mesoscale convective systems (MCS). Here we analyse two different types of MCS originating north and south of the intertropical convergence zone (ITCZ, ∼10 • N), respectively. In addition to the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 152 publications
1
43
0
Order By: Relevance
“…Analyses of aircraft NO x observations and flash data from other tropical regions (e.g., Brazil, West Africa) suggest smaller NO production per flash in the tropics than in midlatitudes (Huntrieser et al, 2008;Huntrieser et al, 2011). Aircraft observations of another Hector storm from SCOUT-O3/ACTIVE also showed larger NO x production per flash than in other tropical events.…”
Section: Discussionmentioning
confidence: 92%
“…Analyses of aircraft NO x observations and flash data from other tropical regions (e.g., Brazil, West Africa) suggest smaller NO production per flash in the tropics than in midlatitudes (Huntrieser et al, 2008;Huntrieser et al, 2011). Aircraft observations of another Hector storm from SCOUT-O3/ACTIVE also showed larger NO x production per flash than in other tropical events.…”
Section: Discussionmentioning
confidence: 92%
“…This may explain lower CO concentrations measured in the UT in the CONV case. Furthermore, Huntrieser et al (2011) showed higher CO, measured by the DLR aircraft, in outflow of MCS observed over southern forests than over the Sahel region.…”
Section: Comparison With Amma Datamentioning
confidence: 87%
“…Based on analysis of DLR measurements, Huntrieser et al (2011) showed that convective uplift of local emissions over West Africa can have a significant impact on UT chemical composition thereby contributing to observed CO enhancements. As demonstrated by several studies (Stohl et al, 2002;Lawrence et al, 2003;Barret et al, 2008), westward transport of Asian pollution by the TEJ may also impact the composition of the African UT.…”
Section: Comparison With Amma Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the factor-of-four uncertainty currently associated with the global LNO x source strength stems primarily from the uncertainty in the global mean NO x production per flash. Several methods have been used to estimate this quantity: theoretical estimates [Price et al, 1997;Koshak et al, 2014], laboratory experiments ], cloud-resolving model simulations constrained by lightning flash observations and anvil NO x measurements [DeCaria et al, 2005;Ott et al, 2007Ott et al, , 2010Cummings et al, 2013], analyses of aircraft data [Huntrieser et al, 2008[Huntrieser et al, , 2009[Huntrieser et al, , 2011, and analyses of satellite observations [Beirle et al, 2004[Beirle et al, , 2006[Beirle et al, , 2010Bucsela et al, 2010]. NO x production estimates from these studies vary from 30 to 1100 mol flash À1 , though most estimates fall between 100 and 500 mol flash…”
mentioning
confidence: 99%